Francisella tularensis Periprosthetic Joint Infections Diagnosed with Growth in Cultures - Chrdle, Aleš; Trnka, Tomáš; Musil, David; Fucentese, Sandro F; Bode, Peter; Keller, Peter M; Achermann, Yvonne (Journal of clinical microbiology, 2019)
Tularemia caused by Francisella tularensis is a zoonotic infection of the Northern Hemisphere that mainly affects the skin, lymph nodes, bloodstream, and lungs. Other manifestations of tularemia are very rare, especially those with musculoskeletal involvement. Presenting in 2016, we diagnosed two cases of periprosthetic knee joint infections (PJI) caused by Francisella tularensis in Europe (one in Switzerland and one in the Czech Republic). We found only two other PJI cases in the literature, another knee PJI diagnosed 1999 in Ontario, Canada, and one hip PJI in Illinois, USA, in 2017. Diagnosis was made in all cases by positive microbiological cultures after 3, 4, 7, and 12 days. All were successfully treated, two cases by exchange of the prosthesis, one with debridement and retention, and one with repeated aspiration of the synovial fluid only. Antibiotic treatment was given between 3 weeks and 12 months with either ciprofloxacin-rifampin or with doxycycline alone or doxycycline in combination with gentamicin. Zoonotic infections should be considered in periprosthetic infections in particular in culture-negative PJIs with a positive histology or highly elevated leukocyte levels in synovial aspiration. Here, we recommend prolonging cultivation time up to 14 days, performing specific PCR tests, and/or conducting epidemiologically appropriate serological tests for zoonotic infections, including that for F. tularensis.
Keywords: protilátky bakteriální; Animals; Zoonoses; Female; Francisella tularensis; zoonózy; výsledek terapie; ženské pohlaví; Knee Joint; bakteriologické techniky; infekce spojené s protézou; tularemie; Bacteriological Techniques; lidé; Anti-Bacterial Agents; Prosthesis-Related Infections; synoviální tekutina; Treatment Outcome; Aged, 80 and over; Tularemia; Antibodies, Bacterial; retrospektivní studie; Male; Aged; Synovial Fluid; senioři nad 80 let; senioři; zvířata; mužské pohlaví; antibakteriální látky; kolenní kloub; Retrospective Studies; Humans